REFLEXIVITY IN THE STUDY OF WARFARE: IS THERE ADDED VALUE FOR THE DISCIPLINE OF INTERNATIONAL RELATIONS? - Srdjan Korac (Srpska Politička Misao)
The article examines whether reflectivist approach to epistemology in the study of warfare can amend some weaknesses of the rationalist/positivist canon of mainstream International Relations (IR) theories. The author argues for the existence of a new epistemic situation for the IR researcher: an ontological transformation of the military profession in post-industrial societies that has created a sacralised civic duty to fight in war. The research of warfare is becoming more focused on the individual – who is either a reluctant combatant or a civilian victimised by military operations, but protected by international norms. The author hypothesises that the advantages of reflectivist epistemological viewpoint – embracing standpoint epistemology, situated knowledge, the concept of embodiment, Cynthia Enloe’s claim that “the international is the personal” – may provide a plausible alternative path in the quest for an answer to the question of how we learn about warfare as the central problem of international relations. The analysis shows how reflectivism encourages researchers to identify new, previously “hidden” or marginalised questions and thus expand the scope of inquiry of mainstream IR. The author concludes that, when it comes to the study of warfare in the early twenty-first century, the largest contribution of reflectivist approach to epistemology of IR is in overcoming the shortcomings of the traditionally rigid mainstream epistemological framework of the discipline, providing the grounds for future counter-hegemonic actions.